Downregulation of long noncoding RNA LINC01419 inhibits cell migration, invasion, and tumor growth and promotes autophagy via inactivation of the PI3K/Akt1/mTOR pathway in gastric cancer. (September 2019) - Wang, Lin-Lin; Zhang, Lei; Cui, Xiao-Feng
Background: Accumulating evidence has highlighted the crucial role of long noncoding RNAs (lncRNAs) in the tumorigenesis of gastric cancer (GC), which is the most common gastrointestinal malignancy. The present study aimed to identify the capacity of lncRNA LINC01419 (LINC01419) in GC progression, with the potential mechanism explored. Methods: Highly expressed lncRNAs were identified by in silico analysis, with the LINC01419 expression in GC tissues measured using reverse transcription-quantitative PCR (RT-qPCR). The GC cells were subsequently transfected with siRNA against LINC01419 or Rapamycin (the inhibitor of the mTOR pathway), or both, in order to measure cell migration and invasion in vitro as well as tumor growth and metastasis in vivo . Moreover, the expression of PI3K/Akt1/mTOR pathway-associated factors was determined. Results: LINC01419, highly expressed in GC samples of the Gene Expression Omnibus database, was observed to be markedly upregulated in GC tissues. Moreover, LINC01419 silencing, or PI3K/Akt1/mTOR pathway inhibition, exhibited an inhibitory role in GC cell migration and invasion in vitro, coupled with promoted cell autophagy in vitro, and inhibited tumor growth and metastasis in vivo . It was also revealed that LINC01419 silencing blocked the PI3K/Akt1/mTOR pathway, as proved by decreased extents of Akt1 and mTOR phosphorylation. Conclusions: In conclusion, LINC01419 inhibition may suppress GC cell invasion and migration, and promote autophagy via inhibition of the PI3K/Akt1/mTOR pathway. This provides significant theoretical basis and possibilities for further elucidation of the molecular mechanism of GC and finding new molecular-targeted therapeutic regimens.